2021
DOI: 10.3390/ijerph182312555
|View full text |Cite
|
Sign up to set email alerts
|

How Do Serum Zonulin Levels Change in Gestational Diabetes Mellitus, Pregnancy Cholestasis, and the Coexistence of Both Diseases?

Abstract: We investigated the question of how serum zonulin levels change in intrahepatic cholestasis of pregnancy (ICP) and gestational diabetes mellitus (GDM) and, in the case of the coexistence of ICP and GDM, evaluated the eventual increase in zonulin plasmatic levels. Participants were enrolled for the study between 25 February 2021 and 20 August 2021. The prospective case-control study included: group 1 of 95 pregnant women diagnosed with ICP; group 2 of 110 pregnant women diagnosed with GDM; group 3 of 16 women d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Mokkala et al [36] reported an increase in serum zonulin concentration from early to late pregnancy, suggesting that intestinal permeability is increased as pregnancy proceeds. Previous studies, such as Daneshvar et al [16] or Guvey et al [35], have demonstrated the relationship between zonulin and GDM, showing higher serum zonulin levels in women with GDM compared to non-diabetic pregnant women. Our data showed a significant increase in zonulin during the follow-up in both healthy controls and GDM women treated with insulin; nevertheless, it remained the same in those women with GDM treated with metformin, probably due to the beneficial changes in the composition of gut microbiota.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mokkala et al [36] reported an increase in serum zonulin concentration from early to late pregnancy, suggesting that intestinal permeability is increased as pregnancy proceeds. Previous studies, such as Daneshvar et al [16] or Guvey et al [35], have demonstrated the relationship between zonulin and GDM, showing higher serum zonulin levels in women with GDM compared to non-diabetic pregnant women. Our data showed a significant increase in zonulin during the follow-up in both healthy controls and GDM women treated with insulin; nevertheless, it remained the same in those women with GDM treated with metformin, probably due to the beneficial changes in the composition of gut microbiota.…”
Section: Discussionmentioning
confidence: 91%
“…Dysbiosis produces an increase in intestinal permeability regulated by zonulin, among others. The stimulation of a zonulin release leads to the dissociation of the zonula occludens-1 protein from tight junctions between intestinal epithelial cells, resulting in increased intestinal permeability [35], which can favor the movement of LPS, which are strong inducers of inflammation [17]. Mokkala et al [36] reported an increase in serum zonulin concentration from early to late pregnancy, suggesting that intestinal permeability is increased as pregnancy proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…The association between zonulin levels and impaired glucose metabolism has also been described in patients with obesity [ 62 , 141 , 142 , 143 , 144 ] or insulin resistance associated with polycystic ovary syndrome (PCOS) [ 145 , 146 ]. Moreover, it has recently been shown that elevated levels of zonulin could be a potential predictor of complications related to pregnancy, including gestational diabetes (GDM), intrahepatic cholestasis (ICP), hypertensive disorders (HDP), and adverse perinatal outcomes [ 131 , 147 , 148 , 149 , 150 , 151 , 152 ].…”
Section: Diseases Associated With Altered Zonulin Levelsmentioning
confidence: 99%
“…Es una condición benigna para la paciente, ya que se asocia a náuseas, pérdida de apetito y dolor en el cuadrante superior derecho del abdomen, asociándose con un buen pronóstico en general. Sin embargo, puede afectar negativamente al feto ya que se ha relacionado con parto pre término, sufrimiento fetal agudo, líquido amniótico meconial y óbito (Güvey et al, 2021;López-Pérez et al, 2022). Se considera que esta afección es de origen multifactorial, ya que se ha asociado a condiciones hormonales, ambientales y genéticas (Ferreiro-Fernando et al, 2020).…”
Section: Introductionunclassified